2010
DOI: 10.1109/lmwc.2009.2038552
|View full text |Cite
|
Sign up to set email alerts
|

CMOS RF Power Amplifier for UHF Stationary RFID Reader

Abstract: A CMOS power amplifier (PA) for a UHF (860-960 MHz) stationary RFID reader is presented. To design a high power and power efficient CMOS PA, quasi four pair structure and integrated passive device (IPD) transformers are used. An amplitude modulation is performed through the cascode gate with a pulse shaping filter. The chips are fabricated in a 0.18 m CMOS process and IPD. Measurements show output power of 32.8-33.37 dBm and the power added efficiency (PAE) of 51.8-56.1% with the supply voltage 3.0 V. Index Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Recently, on-chip transformers have become essential in fully-integrated RF CMOS power amplifiers [1][2][3]. In general, this type of transformer serves as an output balun and as a key component of the output matching network in RF CMOS power amplifiers, as shown in Figure 1, assuming that the typical CMOS power amplifier is designed using a differential structure [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, on-chip transformers have become essential in fully-integrated RF CMOS power amplifiers [1][2][3]. In general, this type of transformer serves as an output balun and as a key component of the output matching network in RF CMOS power amplifiers, as shown in Figure 1, assuming that the typical CMOS power amplifier is designed using a differential structure [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the envelope-tracking (ET) technique has become a popular method to enhance the efficiency of the RF front-end system [1][2][3][4][5][6][7][8][9][10][11][12]. The ET technique can efficiently reduce the power consumption in linear RF power amplifiers, which consume the greatest amount of electric power among the circuits of the RF front-end [13][14][15][16][17][18]. Although there have been various obstacles to complete the ET technique, many meaningful works have been proposed to improve and analyze its feasibility [5][6][7][8][9][10][11][12]19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the DAT provides successful solutions for the output matching networks of CMOS power amplifiers. Various studies related to CMOS power amplifiers using a DAT have been reported . Notably, with application of a DAT as the output matching network, the efficiency of the CMOS power amplifier has been dramatically improved.…”
Section: Introductionmentioning
confidence: 99%